Electricity balancing for resilient 100% renewable energy systems on islands: Imported e-fuels versus domestic e-hydrogen on the case of Mauritius - Arachchi, Geethike V.; Keiner, Dominik; Khalili, Siavash; Premarathna, Maheshika H.K.; George, Jino P.; Gulagi, Ashish; Edoo, M.N.; Ah King, Robert T.F.; Meschede, Henning; Breyer, Christian (Energy)

Flexible operation strategies for heat pumps in district heating systems using dynamic electricity prices - Rahlf, Henning Christoph; Divkovic, Denis; Knorr, Lukas; Schlosser, Florian; Meschede, Henning (Energy Conversion and Management)
Electrifying the heating sector is essential for achieving global climate targets like the Paris Agreement’s 1.5 °C goal. In Germany, where 80 % of household energy goes to space heating and hot water, shifting to low-carbon solutions is crucial. Fossil-fuelled district heating networks can incorporate renewable energy via heat pumps, improving efficiency. Although heat pump design typically favours minimal temperature lifts, higher lifts can be economically viable with low electricity prices and abundant renewables. Adding thermal energy storage boosts operational flexibility. This study explores a flexible heat pump operation incorporating part load behaviour with a thermal energy storage in a German city’s district heating system to minimise costs and carbon dioxide emissions. Using a mixed-integer linear programming model, it examines the impact of temperature adjustments and storage on system efficiency. The results show that the integration of a heat pump in a district heating system reduces operating costs. Compared to a supply without a heat pump, with levelised cost of heating of 9.98 cent/kWhth and a fixed operating mode with costs between 9.96 cent/kWhth and 11.49 cent/kWhth, the flexible use results in lowest costs of 9.85 cent/kWhth, while also reducing overall CO2 emissions. Using a full factorial sensitivity analysis, the levelised cost of heating ranged between 9.15 cent/kWhth in the best case and 10.37 cent/kWhth in the worst case for the selected configuration.
Keywords: Heat transition; Optimisation; Temperature flexibility; Decarbonisation; Multi energy

Analysis of bidirectional EV charging infrastructures within industrial DC grids - Rahlf, Henning Christoph; Knorr, Lukas; Althoff, Simon; Meschede, Henning (Smart Energy)
Industrial electrification is increasing to reduce fossil fuel dependence, alongside a growing share of volatile renewables. A secure and reliable energy supply is crucial for industry, leading to a shift from centralised to decentralised grid structures. DC microgrids becoming increasingly popular in industry, since they enable energy recuperation from braking, reduce components and cables, and integrate storage and local generation to manage supply interruptions or peak loads. EVs add further synergies by serving as mobile storage units, helping to store and redistribute locally generated renewable energy. This paper analyses how EV integration in droop-controlled DC grids can contribute to a more stable, low-emission and peak-reduced load profile to the supply grid through load shifting and bridge interruptions. A droop-controlled DC grid model has been developed, incorporating an EV charging park based on probability functions. Scalable scenarios allow for diverse condition analysis using an energy management system that utilises fuzzy logic and sequential MILP optimisation. It has been shown that a 7% improvement of coefficient represented grid-serving behaviour is possible by load shifting. It has also been demonstrated that an optimised EMS can reduce the demand-based CO2 emissions by 41kg for a representative day compared to a fuzzy logic EMS. At the same time peak load is decreased yielding a more constant residual load. These results highlight the potential of a controlled bidirectional charging infrastructure in DC grids and underscore the need to explicitly consider charging processes to ensure a residual load as constant as possible.
Keywords: DC-grid; Droop control; Grid-serving behaviour; Grid stability; Bidirectional charging; Sequential decision; MILP optimisation

Towards Stakeholder-Aware Demand-Side management assessment in heterogeneous residential Microgrids: A Multi-Agent approach - Henne, Kevin; Rahlf, Henning Christoph; Naumann, Marius; Meschede, Henning (Energy Conversion and Management: X)
Expanding renewable energy sources is essential for a sustainable energy supply but challenges grid stability, as the volatility of solar and wind causes periods of over- and undersupply. Private households are central to this transition, combining dynamic consumption with decentralised generation. This paper presents a multi-agent microgrid simulation built on the Mesa framework, focusing on the heterogeneous objectives and technological capabilities of residential participants. Households are modelled as autonomous agents with individual strategies, while a dedicated “grid agent” represents the distribution system operator and regulates the microgrid in a grid-supportive manner. The emission factor serves as the key indicator for grid-friendly behaviour. Results show that in summer, unmanaged PV feed-in from heterogeneous households causes substantial grid stress and balancing effort for the distribution system operator. Dynamic electricity prices can incentivise grid-friendly dispatch, but their effectiveness depends on the correlation between price signals and renewable availability and cannot guarantee grid-supportive behaviour alone. The grid agent reliably improves the grid-supportive coefficient, yet its operating strategy, for instance additional peak-reduction objectives, can interfere with price-based incentives. Effective demand-side management therefore requires careful analysis of stakeholder interactions. Building on this insight, thepaper provides a basic framework for the design, implementation, and assessment of both integrated and individual energy management strategies within a microgrid environment. By simulating the dynamic interactions among system participants and strategies, it enables comprehensive evaluation of their collective impact on the grid, supporting the development of robust solutions for future electricity networks.
Keywords: Microgrid; Decentralised Energy Systems; Multi-Agent System; Residential Demand-Side Management; Optimisation

Electrification and flexibility of process heat in energy system modelling: A review - Knorr, Lukas; Buchenau, N.; Schlosser, Florian; Divkovic, Denis; Prina, M.G.; Meschede, Henning (Renewable and Sustainable Energy Reviews)

Energy efficiency improvement for decarbonization in manufacturing industry: A review - Naumann, Marius; Ostermann, Moritz; Buchenau, Nadja; Oetzel, Jannik; Schlosser, Florian; Meschede, Henning; Tröster, Thomas (Energy Conversion and Management)

From demand to action: Analysing building emissions and refurbishment scenarios towards climate neutrality - Kirschbaum, Julia; Divkovic, Denis; Meschede, Henning (Applied Energy)

Modular Energy Demand Modeling of Manufacturing Processes for Energy Efficiency Improvement - Naumann, Marius; Henne, Kevin; Ostermann, Moritz; Schlosser, Florian; Meschede, Henning (Procedia CIRP)

Integrated and demand-responsive energy futures in the context of sustainable development of energy systems - Meschede, Henning; Knorr, Lukas; Piacentino, Antonio; Markovska, Natasa; Duic, Neven (Energy)

On the impact of various mobility concepts on integrated energy systems - Meschede, Henning; Knorr, Lukas (e-Prime - Advances in Electrical Engineering, Electronics and Energy)

Improvement of Wind Power Utilization Through Flexible Operation of Data Center in Wind Parks - Ahmadi, Mehdi; Knorr, Lukas; Meschede, Henning (Renewable Energy)

Graph Neural Network Surrogates for Uncertainty Quantification in Multi-Node Energy System modeling - Prina, Matteo Giacomo; Knorr, Lukas; Schlosser, Florian; Meschede, Henning; Misconel Schreiber, Steffi; Manepace, Andrea; Sparber, Wolfram

Effects on dimensioning of heat supply technologies for district heating under consideration of future developments regarding investment costs and emission factors - Divkovic, Denis; Knorr, Lukas; Schwesig, Ramon; Meschede, Henning (Energy)

Optimising Heat Planning: Cost effective heat planning for low carbon district heating - Divkovic, Denis; Kirschbaum, Julia; Rahlf, Henning Christoph; Knorr, Lukas; Meschede, Henning

Integrated renewable energy systems as the basis for sustainable development of energy, water and environment systems - Meschede, Henning; Piacentino, Antonio; Guzovic, Zvonimir; Lund, Henrik; Duic, Neven (Energy)

Energy Flexibility and Electrification of Industrial Process Heat: A Review - Knorr, Lukas; Schlosser, Florian; Divkovic, Denis; Buchenau, Nadja; Meschede, Henning

Flexible operation and integration of high-temperature heat pumps using large temperature glides - Knorr, Lukas; Schlosser, Florian; Horstmann, Nils; Divkovic, Denis; Meschede, Henning (Applied Energy)

Assessment of Energy Efficiency and Flexibility Measures in Electrified Process Heat Generation Based on Simulations in the Animal Feed Industry - Knorr, Lukas; Schlosser, Florian; Meschede, Henning (Journal of Sustainable Development of Energy, Water and Environment Systems)
Keywords: Energy Engineering and Power Technology; Water Science and Technology; Environmental Science (miscellaneous); Renewable Energy; Sustainability and the Environment

Hybrid renewable energy utility systems for industrial sites: A review - Walmsley, Timothy Gordon; Philipp, Matthias; Picón-Núñez, Martín; Meschede, Henning; Taylor, Matthew Thomas; Schlosser, Florian; Atkins, Martin John (Renewable and Sustainable Energy Reviews)
Keywords: Renewable Energy; Sustainability and the Environment

Carbon insetting as a measure to raise supply chain energy efficiency potentials: Opportunities and challenges - Ebersold, Felix; Hechelmann, Ron-Hendrik; Holzapfel, Peter; Meschede, Henning (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment